Composites Based On Conductive Polymer With Carbon Nanotubes In DMMP Gas Sensors – An Overview - Abdullah, Norli; Mohamad, Imran Syakir; N.M., Nurazzi; M.M., Harussani; N.D., Siti Zulaikha; A.H., Norhana (Industrial Chemistry Research Institute, 2021)
A number of recent terrorist attacks make it clear that rapid response, high sensitivity and stability are essential in the development of chemical sensors for the detection of chemical warfare agents. Nerve agent sarin [2-(fluoro-methyl-phosphoryl) oxypropane] is an organophosphate (OP) compound that is recognized as one of the most toxic chemical warfare agents. Considering sarin’s high toxicity, being odorless and colorless, dimethyl methylphosphonate (DMMP) is widely used as its simulant in the laboratory because of its similar chemical structure and much lower toxicity. Thus, this review serves to introduce the development of a variety of fabricated chemical sensors as potential sensing materials for the detection of DMMP in recent years. Furthermore, the research and application of carbon nanotubes in DMMP polymer sensors, their sensitivity and limitation are highlighted. For sorption-based sensors, active materials play crucial roles in improving the integral performances of sensors. The novel active materials providing hydrogen-bonds between the polymers and carbon nanotubes are the main focus in this review.